2023
DOI: 10.3390/jcs7010031
|View full text |Cite
|
Sign up to set email alerts
|

Impact Resistant Flax Fiber Fabrics Using Shear Thickening Fluid

Abstract: Shear thickening fluids (STFs) have been shown to improve the effectiveness of fabrics used in soft body armor applications. They are used to increase the puncture and ballistic impact resistance of Kevlar® fabrics. However, the effect of using STFs with natural fabrics such as flax appears to have never been studied. Similarly, the hybridization of different fabric types impregnated with STF has also only undergone limited study. The rheology of STFs at varying concentrations of nanosilica dispersed in polyet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…STF behaves as a solid-like material under applied stress due to increasing viscosity, and when the loading is removed from the medium, the STF turns to the initial liquid state. Due to the excellent energy absorption and energy dissipation characteristics of STF, it has been widely used in the Li-ion batteries [ 4 ], wearable devices [ 5 ], triboelectric nanogenerator (TENG) [ 6 ], protective structures [ 7 , 8 ] and some novel applications [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…STF behaves as a solid-like material under applied stress due to increasing viscosity, and when the loading is removed from the medium, the STF turns to the initial liquid state. Due to the excellent energy absorption and energy dissipation characteristics of STF, it has been widely used in the Li-ion batteries [ 4 ], wearable devices [ 5 ], triboelectric nanogenerator (TENG) [ 6 ], protective structures [ 7 , 8 ] and some novel applications [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…To improve the impact resistance of textile, different STFs were prepared for the high performance fabric composites [ 50 ]. Some approaches to improve the ballistic performance including surface treatments and modifications of fabrics in STF-based soft body armor were elucidated [ 11 , 51 ]. The applications of various STF impregnated fabric composites and the STFs’ contribution on improving the impact, ballistic and stab resistance performance were investigated by many researchers [ 21 , 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…These unique properties are utilized in combination with materials like fibers/ fabrics to enhance impact resistance and vibration control devices, 1 which in turn are used in the applications in smart buildings, smart fabrics, shock absorbers, and used in liquid body armor, a type of "soft armor" designed to protect against ballistic threats while maintaining mobility. [2][3][4][5][6][7] High-performance synthetic fibers such as aramid, nylon, and carbon fibers are typically employed in these applications along with the STF. 8,9 In a typical rheological curve of viscosity vs shear rate for a STF, there are four characteristics zones namely (i) Newtonian region, (ii) shear thinning region (iii) shear thickening region, and finally (iv) second shear thinning region.…”
Section: Introductionmentioning
confidence: 99%
“…Shear stiffening materials, such as shear thickening gels [1][2][3][4], shear stiffening elastomers [5,6] and shear thickening * Authors to whom any correspondence should be addressed. fluids (STFs) [7][8][9][10][11], are desired to be applied in many industries, such as body armour, smart structures because of their rate-dependent modulus or viscosity. STFs are always dense suspensions consisting of a certain fraction of micron or submicron particles suspended in a liquid medium, such as oobleck (cornstarch-water suspension) [12], chilled caramel topping [13] or silica-polyethylene glycol [14].…”
Section: Introductionmentioning
confidence: 99%
“…Over decades, it has been found that the usage of STFs can improve the ballistic performance [7,8,[24][25][26], stab resistance [27][28][29][30] and energy absorption [31][32][33] of fabrics for the lightweight and flexible enhancement. The studies [34][35][36][37][38] demonstrated that the improved performance of the STF-treated fabrics was ascribed to the increase in friction between yarns, which was investigated by the yarn pull-out tests and was simulated by several finite element models.…”
Section: Introductionmentioning
confidence: 99%